2012
DOI: 10.1002/pen.23350
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of processing conditions on the thermal, rheological and mechanical behavior of polypropylene nanocomposites

Abstract: The use of polypropylene (PP)‐layered silicate nanocomposite has attracted great interest in the polymer industry over the last years. On one hand, PP is widely used in many fields of applications because of good performance and cost. On the other hand, the major advantage of layered silicate nanofiller in the polymer matrix is the small amount of filler (<5 wt%) needed to enhance various properties such as Young's modulus. The most commonly used layered silicates are organomodified montmorillonite (MMT). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…This complies that the polymer chains in contact with the nanofiller develop a much higher Young's modulus than the polymer matrix around [53]. Mattausch et al [52] showed that the highest values of the Young's modulus are achieved with lower rotation speed, therefore low shear effect and the formation of stationary vortexes at the rotors. In these investigations, the residence time has marginal influence on the Young's modulus.…”
Section: Online Extensional Rheometry With the Help Of Rheotens Equipmentioning
confidence: 71%
See 1 more Smart Citation
“…This complies that the polymer chains in contact with the nanofiller develop a much higher Young's modulus than the polymer matrix around [53]. Mattausch et al [52] showed that the highest values of the Young's modulus are achieved with lower rotation speed, therefore low shear effect and the formation of stationary vortexes at the rotors. In these investigations, the residence time has marginal influence on the Young's modulus.…”
Section: Online Extensional Rheometry With the Help Of Rheotens Equipmentioning
confidence: 71%
“…[51], the Rheotens tensile tester was connected to a corotating twinscrew extruder TSK 30/40D of Theysohn in combination with a melt pump. Mattausch et al [52] summarized two mechanisms for the improvement of the Young's modulus. The investigations were performed on two different screw geometries.…”
Section: Online Extensional Rheometry With the Help Of Rheotens Equipmentioning
confidence: 99%
“…Polypropylene (PP) is one of the most widely used thermoplastics, with applications in several segments, such as in the automotive industry, electrical and electronics, construction, packaging etc. . In their formulation, materials based on PP usually contain inorganic reinforcing fillers in order to improve their properties …”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP) is one of the most widely used thermoplastics, with applications in several segments, such as in the automotive industry, electrical and electronics, construction, packaging etc.. [1][2][3][4][5][6][7][8] In their formulation, materi-als based on PP usually contain inorganic reinforcing fillers in order to improve their properties. [7][8][9][10][11][12] Carbon nanotubes are very resistant synthetic nanofillers and provide excellent mechanical properties. Polyolefin nanocomposites containing single wall (SWCNT) and multi-walled (MWCNT) carbon nanotubes have been extensively researched to increase the electrical, thermal, and mechanical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well explored for its potential application as nanofillers for improving the mechanical and thermal properties of the guest polymers [2][3][4]. However, it was found that while MMT can increase the tensile strength and Young's modulus of the host polymer, the elongation at break was considerably decreased [5,6].…”
Section: Introductionmentioning
confidence: 99%